Application of dielectric barrier discharge and plasma-chemical reactor for water purification from NH₄OH - Taran, V.S.; Garkusha, I.E.; Krasnyj, V.V.; Taran, A.V.; Lozina, A.S.; Chechelnitskyi, O.G.; Boldyriev, I.M.; Romaniuk, S.P. (Вопросы атомной науки и техники, 2020)
Water purification from ammonium hydroxide was carried out by using two methods of processing: treatment with ozone generated by a dielectric barrier discharge (DBD) as well as processing in plasma-chemical reactor equipped with a water electrode and a diaphragm, where the main oxidation factors were OH hydroxyl radicals. The volume of the treated aqueous solution was 300 ml and the NH₄OH concentration was 0.025 ml in both cases. The phenolphthalein test was used for visual analysis of the content of an aqueous solution of ammonia in water. The ozone concentration was about 5.8 mg/l in water with ozone injection from an ozone generator and 0.7 mg/l in a plasma-chemical reactor, respectively. The analysis of OH and NO radicals in the water-air gap of the plasma-chemical reactor was carried out using a spectrometer operated in the range of 200…800 nm. Очищення води від гідроксиду амонію проводилося двома способами: обробкою озоном, що генерується діелектричним бар’єрним розрядом (ДБР), і обробкою в плазмохімічному реакторі, обладнаному водяним електродом і діафрагмою, в якому основним чинником окислення були гідроксильні радикали ОН. Обсяг обробленого водного розчину становив 300 мл, а концентрація NH₄OH становила 0,025 мл в обох випадках. Фенолфталеїновий тест використовували для візуального аналізу змісту водного розчину аміаку у воді. Концентрація озону становила близько 5,8 мг/л у воді при введенні озону з генератора озону і 0,7 мг/л в плазмохімічному реакторі відповідно. Аналіз радикалів OH і NO в водно-повітряному проміжку плазмохімічного реактора проводився на спектрометрі, що працює в діапазоні 200…800 нм. Очистка воды от гидроксида аммония проводилась двумя способами: обработкой озоном, генерируемым диэлектрическим барьерным разрядом (ДБР), и обработкой в плазмохимическом реакторе, оборудованном водяным электродом и диафрагмой, в котором основным фактором окисления являлись гидроксильные радикалы ОН. Объем обработанного водного раствора составлял 300 мл, а концентрация NH₄OH составляла 0,025 мл в обоих случаях. Фенолфталеиновый тест использовали для визуального анализа содержания водного раствора аммиака в воде. Концентрация озона составляла около 5,8 мг/л в воде при вводе озона из генератора озона и 0,7 мг/л в плазмохимическом реакторе соответственно. Анализ радикалов OH и NO в водно-воздушном зазоре плазмохимического реактора проводился на спектрометре, работающем в диапазоне 200…800 нм.